Persistence in youth unemployment - Caporale, Guglielmo Maria; Gil-Alana, Luis A. (Berlin, 2012)
"This paper examines the degree of persistence of youth unemployment (total, male and female) in twenty-four countries by using two alternative measures: the AR coefficient and the fractional differencing parameter, based on short- and longmemory processes respectively. The evidence suggests that persistence is particularly high in Japan and some EU countries such as Spain, Portugal, Ireland and Finland, where appropriate policy actions are of the essence. Specifically, active labour market policies are necessary to prevent short-term unemployment from becoming structural (long-term)."